The importance of isometric maximum strength and peak rate-of-force development in sprint cycling - Stone, M. H.; Sands, W. A.; Carlock, J.; Callan, S.; Dickie, D.; Daigle, K.; Cotton, J.; Smith, S. L.; Hartman, M. (The Journal of Strength and Conditioning Research, 2004)
This study was designed to investigate the relationship of whole-body maximum strength to variables potentially associated with track sprint-cycling success. These variables included body composition, power measures, coach's rank, and sprint-cycling times. The study was carried out in 2 parts. The first part (n = 30) served as a pilot for the second part (n = 20). Subjects for both parts ranged from international-caliber sprint cyclists to local-level cyclists. Maximum strength was measured using an isometric midthigh pull (IPF). Explosive strength was measured as the peak rate-of-force development (IPRFD) from the isometric force-time curve. Peak power was estimated from countermovement (CMJPP) and static vertical jumps (SJPP) and measured by modified Wingate tests. Athletes were ranked by the U.S. national cycling coach (part 1). Sprint times (from a standing start) were measured using timing gates placed at 25, 82.5, 165, 247.5, and 330 m of an outdoor velodrome (part 2). Maximum strength (both absolute and body-mass corrected) and explosive strength were shown to be strongly correlated with jump and Wingate power. Additionally, maximum strength was strongly correlated with both coach's rank (parts 1 and 2) and sprint cycling times (part 2). The results suggest that larger, stronger sprint cyclists have an advantage in producing power and are generally faster sprint cyclists.